Analysis of The Implementation of Songs and Chants in English Language Learning for Elementary School Students - Eriyani, Yeni Ikawati; Satriyawan, Aziz Nuri; Handaru, Galih Dian Dwi (Borneo Journal of Primary Education, 2025)
This study aims to analyze the implementation of the Songs and Chants method in English language learning for fifth-grade students at MI Al Huda Pengkol and to describe students’ responses toward its application. The research employed a descriptive qualitative approach involving 27 students and one English teacher. Data were collected through observation, interviews, documentation, and focus group discussions, and analyzed using descriptive and triangulation techniques. The results show that the application of songs and chants increases student participation, enhances learning interest, and creates a more active and enjoyable classroom atmosphere. Students find it easier to remember vocabulary and sentence structures due to repetition and rhythm. Of the 27 students, the number who actively spoke English increased from 13 to 23. Challenges include limited facilities, infrastructure, and preparation in selecting and adapting songs according to the curriculum. Overall, this method proves to be an effective and enjoyable alternative for English learning at the Madrasah Ibtidaiyah level. Further research is suggested to develop more structured songs and chants materials.